Analisis Keterampilan Metakognitif Melalui Pembelajaran Inkuiri Terbimbing Materi Struktur dan Fungsi Tumbuhan Kelas VIII - Anggraini, Sefti; Aini, Kurratul; Nurokhman, Amin; Hapida, Yustina (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2024)
Metacognitive skills help students think, manage their knowledge, analyze and solve problems, understand their learning methods and strategies, and think critically. Guided inquiry learning trains students to think critically, analyze, evaluate, and build information based on their acquired knowledge. This study aims to investigate students' metacognitive skills through guided inquiry learning on the material of Plant Structure and Function. The type of research used is Pre-Experiment with One-Group Pretest-posttest design. The sampling technique used saturated samples with a sample size of 19 students. The research instruments used were pretest and posttest questions on metacognitive skills with planning, monitoring, and evaluation indicators. Data analysis used the Wilcoxon non-parametric test. The results of the increase in cognitive skills in the pretest and posttest were indicated by the N-gain value of 0.59 with the Medium category. The results of the data analysis obtained the Asymp value, sig < 0.5, which is 0.00, which means that HI is accepted. This shows that learning using guided inquiry can affect students' metacognitive skills.